Allergic Reactions After the Administration of COVID-19 Vaccines - Bian, Sainan; Li, Lisha; Wang, Zixi; Cui, Le; Xu, Yingyang; Guan, Kai; Zhao, Bin (Frontiers in Public Health, 2022)
Background Data on allergic reactions after the administration of coronavirus disease (COVID-19) vaccines are limited. To analyze reports of allergic reactions after COVID-19 vaccine administration. Methods The Vaccine Adverse Event Reporting System database was searched for reported allergic reactions after the administration of any of the COVID-19 vaccines from December 2020 to June 2021. After data mapping, the demographic and clinical characteristics of the reported cases were analyzed. Potential factors associated with anaphylaxis were evaluated using multivariable logistic regression models. Results In total, 14,611 cases were reported. Most cases of allergic reactions comprised women (84.6%) and occurred after the first dose of the vaccine (63.6%). Patients who experienced anaphylaxis were younger (mean age 45.1±15.6 versus 47.0±16.3 years, P<0.001) and had a higher prevalence of a history of allergy to medications or other products, allergic rhinitis, asthma, and anaphylaxis than those who did not (P<0.05). A history of allergy to medications or other products (odds ratio (OR) 1.632, 95% confidence interval (CI) 1.467–1.816, P<0.001), asthma (OR 1.908, 95%CI 1.677–2.172, P<0.001), anaphylaxis (OR 7.164, 95%CI 3.504–14.646, P<0.001), and age (OR 1.009, 95% CI 1.006–1.012, P<0.001) were potential risk factors for anaphylaxis. Among the 8232 patients with reported outcomes, 16 died. Conclusions Female predominance in allergic reaction cases after the receipt of COVID-19 vaccines was observed. Previous histories of allergy to medications or other products, asthma, or anaphylaxis were risk factors for anaphylaxis post-vaccination. People with these risk factors should be monitored more strictly after COVID-19 vaccination.